2014
DOI: 10.1109/tip.2014.2310126
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Model of Quantized DCT Coefficients: Application in the Steganalysis of Jsteg Algorithm

Abstract: The goal of this paper is to propose a statistical model of quantized discrete cosine transform (DCT) coefficients. It relies on a mathematical framework of studying the image processing pipeline of a typical digital camera instead of fitting empirical data with a variety of popular models proposed in this paper. To highlight the accuracy of the proposed model, this paper exploits it for the detection of hidden information in JPEG images. By formulating the hidden data detection as a hypothesis testing, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 36 publications
0
69
0
2
Order By: Relevance
“…The main motivation is that the statistics of DCT coefficients change with different sensor noises combining with various in-camera processing algorithms. Therefore, this paper exploits a state-of-the-art model of DCT coefficients [29] to accurately extract information at different frequencies and proposes a new fingerprint for camera model identification.…”
Section: Main Contributions Of the Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The main motivation is that the statistics of DCT coefficients change with different sensor noises combining with various in-camera processing algorithms. Therefore, this paper exploits a state-of-the-art model of DCT coefficients [29] to accurately extract information at different frequencies and proposes a new fingerprint for camera model identification.…”
Section: Main Contributions Of the Papermentioning
confidence: 99%
“…• This paper is based on the state-of-the-art statistical model of DCT coefficients [27][28][29] for fingerprint extraction. The parameters (c, d) that characterize the simplified linear relation between two parameters α and β −1 , which are specified in the proposed model of DCT coefficients, are exploited as camera fingerprint for camera model identification.…”
Section: Main Contributions Of the Papermentioning
confidence: 99%
“…Such a result can be explained by the two following reasons: 1) the Laplacian model might be not accurate enough to detect steganagraphy and 2) the assumption that the DCT coefficients of each frequency subband are i. i. d. may be wrong. Recently, it has been shown that the use of the generalised gamma model or an even more accurate model [36,37] allows the designing of a test with very good detection performance. On the opposite, in this paper, it is proposed to challenge the assumption that all the DCT coefficients of a subband are i. i. d.…”
Section: Problem Statementmentioning
confidence: 99%
“…This theorem is of crucial interest to establish the statistical properties of the proposed test [7,22,37,38]. In fact, once the moments have been calculated under both H i , i = {0, 1}, one can normalise under hypothesis H 0 the LR lr (U) as follows:…”
Section: Statistical Performance Of Lrtmentioning
confidence: 99%
“…Detectors from the first category can be guaranteed to be optimal within the chosen cover model and thus designed to maximize the detection power for a prescribed false-alarm probability. However, they are limited to steganographic schemes that introduce easily detectable artifacts into the statistics of DCT coefficients, such as Jsteg 18,22 or OutGuess. 19 However, modern steganographic schemes, example of which is J-UNIWARD 11 and Uniform Embedding Distortion (UED), 5 and many side-informed schemes, such as SI-UNIWARD, 11 Normalized Perturbed Quantization (NPQ), 12 and Entropy-Block Steganography (EBS), 20 do not introduce easily detectable artifacts into the statistics of quantized DCT coefficients.…”
Section: Introductionmentioning
confidence: 99%